Evaluación y comparación de fórmulas de champú elaborado con distintos niveles de leche de cabra - María José, Castelo Latorre (2020)
Shampoo is a detergent solution contains additives for cleaning and maintaining the scalp. Goat milk, has very interesting technological and nutritional characteristics, and could be used in shampoo formulations and improve its properties. This study responds to the need of the microenterprise Development and Innovation Center for the Agricultural Sector (Finca la Jaira), and its objective was to evaluate and compare formulas of shampoo made with different levels of goat's milk. Four shampoo formulas were made at different concentrations of goat milk (0, 10, 20 and 30%) with a storage time of 60 days. The characteristics were evaluated with conditioning and physicochemical tests such as pH, viscosity, foam formation, dirt dispersion, among others. When comparing the formulations made, we obtained that goat milk provides good conditioning performance. Shampoos are within the range of pH 5-7, the viscosity is of a pseudoplastic nature, they have good cleaning, low surface tension, good foam stability, between 20 and 30% solids and a good wetting time. It is concluded that the best formulations were those that used 10 and 20% goat milk, because it maintains its characteristics and does not show protein flocculation and acidification, in addition to the stability of the product is one month. Despite this, more research is required to improve the quality of the shampoo and increase its shelf life.